Intra-financial activities of the business entities - Шишка, Роман Богданович; Мкртичева, Марина Ігорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
Balance and off-balance structural subdividing are considered in the doctrine of the civil and commercial law, and at legislative level too. As the subjects of economic activity can create at its discretion separate subdividing and control their activities on the right of economic guiding or the right of operational management, so it can independently determine the costs of maintaining of the property and of the other subjects which aren’t object of the taxation and as a result are uncontrollable. Therefore the problem consists in naturalization and idealization of these objects.